X-ray photoelectron spectroscopy of graphitic carbon nanomaterials doped with heteroatoms - Susi, Toma; Pichler, Thomas; Ayala, Paola (Beilstein Journal of Nanotechnology, 2015)
X-ray photoelectron spectroscopy (XPS) is one of the best tools for studying the chemical modification of surfaces, and in particular the distribution and bonding of heteroatom dopants in carbon nanomaterials such as graphene and carbon nanotubes. Although these materials have superb intrinsic properties, these often need to be modified in a controlled way for specific applications. Towards this aim, the most studied dopants are neighbors to carbon in the periodic table, nitrogen and boron, with phosphorus starting to emerge as an interesting new alternative. Hundreds of studies have used XPS for analyzing the concentration and bonding of dopants in various materials. Although the majority of works has concentrated on nitrogen, important work is still ongoing to identify its precise atomic bonding configurations. In general, care should be taken in the preparation of a suitable sample, consideration of the intrinsic photoemission response of the material in question, and the appropriate spectral analysis. If this is not the case, incorrect conclusions can easily be drawn, especially in the assignment of measured binding energies into specific atomic configurations. Starting from the characteristics of pristine materials, this review provides a practical guide for interpreting X-ray photoelectron spectra of doped graphitic carbon nanomaterials, and a reference for their binding energies that are vital for compositional analysis via XPS.
Keywords: carbon nanotubes; core level photoemission; graphene; substitutional doping; X-ray photoelectron spectroscopy (XPS)

(untitled) - Kroto, H. W.; Heath, J. R.; O’Brien, S. C.; Curl, R. F.; Smalley, R. E. (Nature, 1985)

Fullerenes and Related Structures - Hirsch, A. (Springer, 1999)

(untitled) - Iijima, S. (Nature, 1991)

(untitled) - Iijima, S.; Ichihashi, T. (Nature, 1993)

(untitled) - Bethune, D. S.; Klang, C. H.; de Vries, M. S.; Gorman, G.; Savoy, R.; Vazquez, J.; Beyers, R. (Nature, 1993)

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Zhang, Y.; Dubonos, S. V.; Grigorieva, I. V.; Firsov, A. A. (Science, 2004)

(untitled) - Novoselov, K. S.; Geim, A. K.; Morozov, S. V.; Jiang, D.; Katsnelson, M. I.; Grigorieva, I. V.; Dubonos, S. V.; Firsov, A. A. (Nature, 2005)

(untitled) - Geim, A. K.; Novoselov, K. S. (Nat. Mater., 2007)

(untitled) - Pauling, L. (J. Am. Chem. Soc., 1931)

(untitled) - Kekulé, A. (Justus Liebigs Ann. Chem., 1866)

(untitled) - Kroto, H. W. (Nature, 1987)

(untitled) - Prato, M. (J. Mater. Chem., 1997)

(untitled) - Peng, B.; Locascio, M.; Zapol, P.; Li, S.; Mielke, S. L.; Schatz, G. C.; Espinosa, H. D. (Nat. Nanotechnol., 2008)

(untitled) - Saito, R.; Fujita, M.; Dresselhaus, G.; Dresselhaus, M. S. (Appl. Phys. Lett., 1992)

(untitled) - Charlier, J.-C.; Blase, X.; Roche, S. (Rev. Mod. Phys., 2007)

(untitled) - Frank, S.; Poncharal, P.; Wang, Z. L.; de Heer, W. A. (Science, 1998)

(untitled) - Hong, S.; Myung, S. (Nat. Nanotechnol., 2007)

(untitled) - Bunch, J. S.; Verbridge, S. S.; Alden, J. S.; van der Zande, A. M.; Parpia, J. M.; Craighead, H. G.; McEuen, P. L. (Nano Lett., 2008)

(untitled) - Lee, C.; Wei, X.; Kysar, J. W.; Hone, J. (Science, 2008)

(untitled) - Zhang, Y.; Tan, Y.-W.; Stormer, H. L.; Kim, P. (Nature, 2005)

(untitled) - Gusynin, V. P.; Sharapov, S. G. (Phys. Rev. Lett., 2005)

(untitled) - Yi, J.-Y.; Bernholc, J. (Phys. Rev. B, 1993)

(untitled) - Stephan, O.; Ajayan, P. M.; Colliex, C.; Redlich, P.; Lambert, J. M.; Bernier, P.; Lefin, P. (Science, 1994)

(untitled) - Ge, M.; Sattler, K. (Appl. Phys. Lett., 1994)

(untitled) - Odom, T. W.; Huang, J.-L.; Kim, P.; Lieber, C. M. (Nature, 1998)

(untitled) - Colliex, C. (J. Electron Microsc., 1996)

(untitled) - Zhao, L.; He, R.; Rim, K. T.; Schiros, T.; Kim, K. S.; Zhou, H.; Gutiérrez, C.; Chockalingam, S. P.; Arguello, C. J.; Pálová, L.; Nordlund, D.; Hybertsen, M. S.; et al. (Science, 2011)

(untitled) - Zhou, W.; Kapetanakis, M.; Prange, M.; Pantelides, S.; Pennycook, S.; Idrobo, J.-C. (Phys. Rev. Lett., 2012)

(untitled) - Ramasse, Q. M.; Seabourne, C. R.; Kepaptsoglou, D.-M.; Zan, R.; Bangert, U.; Scott, A. J. (Nano Lett., 2013)

(untitled) - Bangert, U.; Pierce, W.; Kepaptsoglou, D. M.; Ramasse, Q.; Zan, R.; Gass, M. H.; Van den Berg, J. A.; Boothroyd, C. B.; Amani, J.; Hofsäss, H. (Nano Lett., 2013)

(untitled) - Nicholls, R. J.; Murdock, A. T.; Tsang, J.; Britton, J.; Pennycook, T. J.; Koós, A.; Nellist, P. D.; Grobert, N.; Yates, J. R. (ACS Nano, 2013)

(untitled) - Zhao, L.; Levendorf, M. P.; Goncher, S. J.; Schiros, T.; Palova, L.; Zabet-Khosousi, A.; Rim, K. T.; Gutierrez, C.; Nordlund, D.; Jaye, C.; Hybertsen, M. S.; Reichman, D. R.; et al. (Nano Lett., 2013)

(untitled) - Ayala, P.; Arenal, R.; Rümmeli, M. H.; Rubio, A.; Pichler, T. (Carbon, 2010)

(untitled) - Ayala, P.; Arenal, R.; Loiseau, A.; Rubio, A.; Pichler, T. (Rev. Mod. Phys., 2010)

Graphene and its Interaction with Different Substrates Studied by Angular-Resolved Photoemission Spectroscopy - Enderlein, C. (Freie Universität Berlin, 2010)

(untitled) - Lim, H.; Song, H. J.; Son, M.; Baik, J. Y.; Shin, H.-J.; Choi, H. C. (Chem. Commun., 2011)

(untitled) - Ayala, P.; Miyata, Y.; De Blauwe, K.; Shiozawa, H.; Feng, Y.; Yanagi, K.; Kramberger, C.; Silva, S.; Follath, R.; Kataura, H. (Phys. Rev. B, 2009)

(untitled) - Smith, N. V.; Traum, M. M.; Di Salvo, F. J. (Solid State Commun., 1974)

(untitled) - Himpsel, F. (Adv. Phys., 1983)

(untitled) - Georgakilas, V.; Kordatos, K.; Prato, M.; Guldi, D. M.; Holzinger, M.; Hirsch, A. (J. Am. Chem. Soc., 2002)

(untitled) - Sinnott, S. B. (J. Nanosci. Nanotechnol., 2002)

(untitled) - Sun, Y.-P.; Fu, K.; Lin, Y.; Huang, W. (Acc. Chem. Res., 2002)

(untitled) - Balasubramanian, K.; Burghard, M. (Small, 2005)

(untitled) - Georgakilas, V.; Otyepka, M.; Bourlinos, A. B.; Chandra, V.; Kim, N.; Kemp, K. C.; Hobza, P.; Zboril, R.; Kim, K. S. (Chem. Rev., 2012)

(untitled) - Kuila, T.; Bose, S.; Mishra, A. K.; Khanra, P.; Kim, N. H.; Lee, J. H. (Prog. Mater. Sci., 2012)

(untitled) - Casanovas, J.; Ricart, J. M.; Rubio, J.; Illas, F.; Jiménez-Mateos, J. M. (J. Am. Chem. Soc., 1996)

(untitled) - Cole, R. J.; Macdonald, B. F.; Weightman, P. (J. Electron Spectrosc. Relat. Phenom., 2002)

(untitled) - Kudashov, A. G.; Okotrub, A. V.; Bulusheva, L. G.; Asanov, L. P.; Shubin, Yu. V.; Yudanov, N. F.; Yudanova, L. I.; Danilovich, V. S.; Abrosimov, O. G. (J. Phys. Chem. B, 2004)

(untitled) - Hellgren, N.; Guo, J.; Luo, Y.; Såthe, C.; Agui, A.; Kashtanov, S.; Nordgren, J.; Ågren, H.; Sundgren, J.-E. (Thin Solid Films, 2005)

(untitled) - Cabellos, J. L.; Mowbray, D. J.; Goiri, E.; El-Sayed, A.; Floreano, L.; de Oteyza, D. G.; Rogero, C.; Ortega, J. E.; Rubio, A. (J. Phys. Chem. C, 2012)

(untitled) - Susi, T.; Kaukonen, M.; Havu, P.; Ljungberg, M. P.; Ayala, P.; Kauppinen, E. I. (Beilstein J. Nanotechnol., 2014)

(untitled) - Ruiz-Soria, G.; Pérez Paz, A.; Sauer, M.; Mowbray, D. J.; Lacovig, P.; Dalmiglio, M.; Lizzit, S.; Yanagi, K.; Rubio, A.; Goldoni, A.; Ayala, P.; Pichler, T. (ACS Nano, 2014)

(untitled) - Shirley, E. L. (Phys. Rev. Lett., 1998)

(untitled) - Despoja, V.; Mowbray, D. J.; Vlahović, D.; Marušić, L. (Phys. Rev. B, 2012)

(untitled) - Despoja, V.; Šunjić, M. (Phys. Rev. B, 2013)

(untitled) - Doniach, S.; Šunjić, M. (J. Phys. C, 1970)

(untitled) - Tanuma, S.; Shiratori, T.; Kimura, T.; Goto, K.; Ichimura, S.; Powell, C. J. (Surf. Interface Anal., 2005)

(untitled) - Shirley, D. A. (Phys. Rev. B, 1972)

(untitled) - Tougaard, S. (J. Vac. Sci. Technol., A, 1990)

Theoretical photoionization cross sections from 1 to 1500 keV - Scofield, J. (Lawrence Livermore National Laboratory, 1973)

Handbook of X-ray photoelectron spectroscopy - Moulder, J. F.; Stickle, W. F.; Sobol, P. E.; Bomben, K. D. (Perkin Elmer, 1992)

(untitled) - Prince, K. C.; Ulrych, I.; Peloi, M.; Ressel, B.; Cháb, V.; Crotti, C.; Comicioli, C. (Phys. Rev. B, 2000)

(untitled) - Speranza, G.; Minati, L.; Anderle, M. (J. Appl. Phys., 2007)

(untitled) - Emtsev, K. V.; Speck, F.; Seyller, T.; Ley, L.; Riley, J. D. (Phys. Rev. B, 2008)

(untitled) - Hunt, M. R. C. (Phys. Rev. B, 2008)

(untitled) - Balasubramanian, T.; Andersen, J. N.; Walldén, L. (Phys. Rev. B, 2001)

(untitled) - Scardamaglia, M.; Aleman, B.; Amati, M.; Ewels, C.; Pochet, P.; Reckinger, N.; Colomer, J.-F.; Skaltsas, T.; Tagmatarchis, N.; Snyders, R.; Gregoratti, L.; Bittencourt, C. (Carbon, 2014)

(untitled) - Grüneis, A.; Kummer, K.; Vyalikh, D. V. (New J. Phys., 2009)

(untitled) - Haberer, D.; Vyalikh, D. V.; Taioli, S.; Dora, B.; Farjam, M.; Fink, J.; Marchenko, D.; Pichler, T.; Ziegler, K.; Simonucci, S.; Dresselhaus, M. S.; Knupfer, M.; et al. (Nano Lett., 2010)

(untitled) - Haberer, D.; Giusca, C. E.; Wang, Y.; Sachdev, H.; Fedorov, A. V.; Farjam, M.; Jafari, S. A.; Vyalikh, D. V.; Usachov, D.; Liu, X.; Treske, U.; Grobosch, M.; et al. (Adv. Mater., 2011)

Electronic Properties of Functionalized Graphene Studied With Photoemission Spectroscopy - Haberer, D. (TU Dresden / IWF Dresden, 2012)

(untitled) - Avila, J.; Razado, I.; Lorcy, S.; Fleurier, R.; Pichonat, E.; Vignaud, D.; Wallart, X.; Asensio, M. C. (Sci. Rep., 2013)

(untitled) - Hibino, H.; Kageshima, H.; Kotsugi, M.; Maeda, F.; Guo, F.-Z.; Watanabe, Y. (Phys. Rev. B, 2009)

(untitled) - Merino, P.; Švec, M.; Martinez, J. I.; Jelinek, P.; Lacovig, P.; Dalmiglio, M.; Lizzit, S.; Soukiassian, P.; Cernicharo, J.; Martin-Gago, J. A. (Nat. Commun., 2014)

(untitled) - Riedl, C.; Coletti, C.; Iwasaki, T.; Zakharov, A. A.; Starke, U. (Phys. Rev. Lett., 2009)

(untitled) - Preobrajenski, A. B.; Ng, M. L.; Vinogradov, A. S.; Mårtensson, N. (Phys. Rev. B, 2008)

(untitled) - Rajasekaran, S.; Abild-Pedersen, F.; Ogasawara, H.; Nilsson, A.; Kaya, S. (Phys. Rev. Lett., 2013)

(untitled) - Lizzit, S.; Zampieri, G.; Petaccia, L.; Larciprete, R.; Lacovig, P.; Rienks, E. D. L.; Bihlmayer, G.; Baraldi, A.; Hofmann, P. (Nat. Phys., 2010)

(untitled) - De Blauwe, K.; Mowbray, D. J.; Miyata, Y.; Ayala, P.; Shiozawa, H.; Rubio, A.; Hoffmann, P.; Kataura, H.; Pichler, T. (Phys. Rev. B, 2010)

(untitled) - Choi, H. C.; Kim, S. Y.; Jang, W. S.; Bae, S. Y.; Park, J.; Kim, K. L.; Kim, K. (Chem. Phys. Lett., 2004)

(untitled) - Kim, S. Y.; Lee, J. Y.; Park, J.; Park, C. J.; Lee, C. J.; Shin, H.-J. (Chem. Phys. Lett., 2006)

(untitled) - Schiessling, J.; Kjeldgaard, L.; Rohmund, F.; Falk, L. K. L.; Campbell, E. E. B.; Nordgren, J.; Brühwiler, P. A. (J. Phys.: Condens. Matter, 2003)

(untitled) - Leiro, J.; Heinonen, M.; Laiho, T.; Batirev, I. (J. Electron Spectrosc. Relat. Phenom., 2003)

(untitled) - van Attekum, P. M. T. M.; Wertheim, G. K. (Phys. Rev. Lett., 1979)

(untitled) - Lizzit, S.; Petaccia, L.; Goldoni, A.; Larciprete, R.; Hofmann, P.; Zampieri, G. (Phys. Rev. B, 2007)

(untitled) - Castro Neto, A. H.; Guinea, F.; Peres, N. M. R.; Novoselov, K. S.; Geim, A. K. (Rev. Mod. Phys., 2009)

(untitled) - Zhou, S. Y.; Gweon, G. H.; Fedorov, A. V.; First, P. N.; de Heer, W. A.; Lee, D.-H.; Guinea, F.; Castro Neto, A. H.; Lanzara, A. (Nat. Mater., 2007)

Carbon Nanotubes: Synthesis, Structure, Properties, and Applications - Dresselhaus, M. S.; Dresselhaus, G.; Avouris, P. (Springer, 2001)

(untitled) - Saito, R.; Dresselhaus, G.; Dresselhaus, M. S. (Phys. Rev. B, 2000)

(untitled) - Shen, C.; Brozena, A. H.; Wang, Y. (Nanoscale, 2011)

(untitled) - Krupke, R.; Hennrich, F.; Löhneysen, H.; Kappes, M. (Science, 2003)

(untitled) - Arnold, M.; Green, A.; Hulvat, J.; Stupp, S.; Hersam, M. (Nat. Nanotechnol., 2006)

(untitled) - Yanagi, K.; Iitsuka, T.; Fujii, S.; Kataura, H. (J. Phys. Chem. C, 2008)

(untitled) - Ewels, C.; Glerup, M. (J. Nanosci. Nanotechnol., 2005)

Carbon Nanotubes - Terrones, M.; Souza Filho, A. G.; Rao, A. M. (Doped Carbon Nanotubes: Synthesis, Characterization and Applications, 2008)

(untitled) - Strelko, V. V.; Kuts, V. S.; Thrower, P. A. (Carbon, 2000)

(untitled) - Cruz-Silva, E.; Cullen, D. A.; Gu, L.; Romo-Herrera, J. M.; Muñoz-Sandoval, E.; López-Urías, F.; Sumpter, B. G.; Meunier, V.; Charlier, J.-C.; Smith, D. J.; Terrones, H.; Terrones, M. (ACS Nano, 2008)

(untitled) - Cruz-Silva, E.; López-Urías, F.; Muñoz-Sandoval, E.; Sumpter, B. G.; Terrones, H.; Charlier, J.-C.; Meunier, V.; Terrones, M. (ACS Nano, 2009)

(untitled) - Krstić, V.; Ewels, C. P.; Wågberg, T.; Ferreira, M. S.; Janssens, A. M.; Stéphan, O.; Glerup, M. (ACS Nano, 2010)

(untitled) - Some, S.; Kim, J.; Lee, K.; Kulkarni, A.; Yoon, Y.; Lee, S.; Kim, T.; Lee, H. (Adv. Mater., 2012)

(untitled) - Garcia, A. G.; Baltazar, S. E.; Castro, A. H. R.; Robles, J. F. P.; Rubio, A. (J. Comput. Theor. Nanosci., 2008)

(untitled) - Sumpter, B. G.; Huang, J.; Meunier, V.; Romo-Herrera, J. M.; Cruz-Silva, E.; Terrones, H.; Terrones, M. (Int. J. Quantum Chem., 2009)

(untitled) - Jiang, H.; Zhang, D.; Wang, R. (Nanotechnology, 2009)

(untitled) - Denis, P. A. (Chem. Phys. Lett., 2010)

(untitled) - Yang, S.; Zhi, L.; Tang, K.; Feng, X.; Maier, J.; Müllen, K. (Adv. Funct. Mater., 2012)

(untitled) - Audiffred, M.; Elías, A. L.; Gutiérrez, H. R.; López-Urías, F.; Terrones, H.; Merino, G.; Terrones, M. (J. Phys. Chem. C, 2013)

(untitled) - Terrones, H.; Lv, R.; Terrones, M.; Dresselhaus, M. S. (Rep. Prog. Phys., 2012)

(untitled) - Yudasaka, M.; Kikuchi, R.; Ohki, Y.; Yoshimura, S. (Carbon, 1997)

(untitled) - Sen, R.; Satishkumar, B. C.; Govindaraj, A.; Harikumar, K. R.; Renganathan, M. K.; Rao, C. N. R. (J. Mater. Chem., 1997)

(untitled) - Terrones, M.; Terrones, H.; Grobert, N.; Hsu, W. K.; Zhu, Y. Q.; Hare, J. P.; Kroto, H. W.; Walton, D. R. M.; Kohler-Redlich, P.; Rühle, M.; Zhang, J. P.; Cheetham, A. K. (Appl. Phys. Lett., 1999)

(untitled) - Glerup, M.; Steinmetz, J.; Samaille, D.; Stéphan, O.; Enouz, S.; Loiseau, A.; Roth, S.; Bernier, P. (Chem. Phys. Lett., 2004)

(untitled) - Lin, H.; Lagoute, J.; Chacon, C.; Arenal, R.; Stéphan, O.; Repain, V.; Girard, Y.; Enouz, S.; Bresson, L.; Rousset, S.; Loiseau, A. (Phys. Status Solidi B, 2008)

(untitled) - Keskar, G.; Rao, R.; Luo, J.; Hudson, J.; Chen, J.; Rao, A. M. (Chem. Phys. Lett., 2005)

(untitled) - Min, Y.-S.; Bae, E. J.; Asanov, I. P.; Kim, U. J.; Park, W. (Nanotechnology, 2007)

(untitled) - Villalpando-Paez, F.; Zamudio, A.; Elias, A. L.; Son, H.; Barros, E. B.; Chou, S. G.; Kim, Y. A.; Muramatsu, H.; Hayashi, T.; Kong, J.; Terrones, H.; Dresselhaus, G.; et al. (Chem. Phys. Lett., 2006)

(untitled) - Ayala, P.; Grüneis, A.; Gemming, T.; Büchner, B.; Rümmeli, M. H.; Grimm, D.; Schumann, J.; Kaltofen, R.; Freire, F., Jr; Fonseca Filho, H. D.; Pichler, T. (Chem. Mater., 2007)

(untitled) - Ayala, P.; Grüneis, A.; Gemming, T.; Grimm, D.; Kramberger, C.; Rümmeli, M. H.; Freire, F. L., Jr; Kuzmany, H.; Pfeiffer, R.; Barreiro, A.; Büchner, B.; Pichler, T. (J. Phys. Chem. C, 2007)

(untitled) - Ayala, P.; Freire, F. L., Jr; Rümmeli, M. H.; Grüneis, A.; Pichler, T. (Phys. Status Solidi B, 2007)

(untitled) - Elías, A. L.; Ayala, P.; Zamudio, A.; Grobosch, M.; Cruz-Silva, E.; Romo-Herrera, J. M.; Campos-Delgado, J.; Terrones, H.; Pichler, T.; Terrones, M. (J. Nanosci. Nanotechnol., 2010)

(untitled) - Ibrahim, E. M. M.; Khavrus, V. O.; Leonhardt, A.; Hampel, S.; Oswald, S.; Rümmeli, M. H.; Büchner, B. (Diamond Relat. Mater., 2010)

(untitled) - Liu, Y.; Jin, Z.; Wang, J.; Cui, R.; Sun, H.; Peng, F.; Wei, L.; Wang, Z.; Liang, X.; Peng, L. (Adv. Funct. Mater., 2011)

(untitled) - Susi, T.; Nasibulin, A. G.; Ayala, P.; Tian, Y.; Zhu, Z.; Jiang, H.; Roquelet, C.; Garrot, D.; Lauret, J.-S.; Kauppinen, E. I. (Phys. Status Solidi B, 2009)

(untitled) - Pint, C. L.; Sun, Z.; Moghazy, S.; Xu, Y.-Q.; Tour, J. M.; Hauge, R. H. (ACS Nano, 2011)

(untitled) - Koós, A. A.; Dillon, F.; Nicholls, R. J.; Bulusheva, L.; Grobert, N. (Chem. Phys. Lett., 2012)

(untitled) - Thurakitseree, T.; Kramberger, C.; Zhao, P.; Aikawa, S.; Harish, S.; Chiashi, S.; Einarsson, E.; Maruyama, S. (Carbon, 2012)

(untitled) - Wei, D.; Liu, Y.; Wang, Y.; Zhang, H.; Huang, L.; Yu, G. (Nano Lett., 2009)

(untitled) - Usachov, D.; Vilkov, O.; Grüneis, A.; Haberer, D.; Fedorov, A.; Adamchuk, V. K.; Preobrajenski, A. B.; Dudin, P.; Barinov, A.; Oehzelt, M.; Laubschat, C.; Vyalikh, D. V. (Nano Lett., 2011)

(untitled) - Lin, Y.-C.; Lin, C.-Y.; Chiu, P.-W. (Appl. Phys. Lett., 2010)

(untitled) - Joucken, F.; Tison, Y.; Lagoute, J.; Dumont, J.; Cabosart, D.; Zheng, B.; Repain, V.; Chacon, C.; Girard, Y.; Botello-Méndez, A. R.; Rousset, S.; Sporken, R.; et al. (Phys. Rev. B, 2012)

(untitled) - Wang, H.; Maiyalagan, T.; Wang, X. (ACS Catal., 2012)

(untitled) - Trasobares, S.; Stephan, O.; Colliex, C.; Hsu, W. K.; Kroto, H. W.; Walton, D. R. M. (J. Chem. Phys., 2002)

(untitled) - Schulte, K.; Wang, L.; Moriarty, P. J.; Prassides, K.; Tagmatarchis, N. (J. Chem. Phys., 2007)

(untitled) - Susi, T.; Kaskela, A.; Zhu, Z.; Ayala, P.; Arenal, R.; Tian, Y.; Laiho, P.; Mali, J.; Nasibulin, A. G.; Jiang, H.; Lanzani, G.; Stephan, O.; et al. (Chem. Mater., 2011)

(untitled) - Barzegar, H. R.; Gracia-Espino, E.; Sharifi, T.; Nitze, F.; Wågberg, T. (J. Phys. Chem. C, 2013)

(untitled) - Kim, S. Y.; Lee, J.; Na, C. W.; Park, J.; Seo, K.; Kim, B. (Chem. Phys. Lett., 2005)

(untitled) - Panchakarla, L. S.; Govindaraj, A.; Rao, C. N. R. (ACS Nano, 2007)

(untitled) - Choi, H. C.; Park, J.; Kim, B. (J. Phys. Chem. B, 2005)

(untitled) - Point, S.; Minea, T.; Bouchet-Fabre, B.; Granier, A.; Turban, G. (Diamond Relat. Mater., 2005)

(untitled) - Droppa, R., Jr; Ribeiro, C. T. M.; Zanatta, A. R.; dos Santos, M. C.; Alvarez, F. (Phys. Rev. B, 2004)

(untitled) - Ghosh, K.; Kumar, M.; Maruyama, T.; Ando, Y. (J. Mater. Chem., 2010)

(untitled) - Ghosh, K.; Kumar, M.; Maruyama, T.; Ando, Y. (Carbon, 2010)

(untitled) - Lv, R.; Li, Q.; Botello-Méndez, A. R.; Hayashi, T.; Wang, B.; Berkdemir, A.; Hao, Q.; Elías, A. L.; Cruz-Silva, R.; Gutiérrez, H. R.; Kim, Y. A.; Muramatsu, H.; et al. (Sci. Rep., 2012)

(untitled) - Schiros, T.; Nordlund, D.; Pálová, L.; Prezzi, D.; Zhao, L.; Kim, K. S.; Wurstbauer, U.; Gutiérrez, C.; Delongchamp, D.; Jaye, C.; Fischer, D.; Ogasawara, H.; et al. (Nano Lett., 2012)

(untitled) - Kondo, T.; Casolo, S.; Suzuki, T.; Shikano, T.; Sakurai, M.; Harada, Y.; Saito, M.; Oshima, M.; Trioni, M. I.; Tantardini, G. F.; Nakamura, J. (Phys. Rev. B, 2012)

(untitled) - Meyer, J. C.; Kurasch, S.; Park, H. J.; Skakalova, V.; Künzel, D.; Groü, A.; Chuvilin, A.; Algara-Siller, G.; Roth, S.; Iwasaki, T.; Starke, U.; Smet, J. H.; et al. (Nat. Mater., 2011)

(untitled) - Susi, T.; Kotakoski, J.; Arenal, R.; Kurasch, S.; Jiang, H.; Skakalova, V.; Stephan, O.; Krasheninnikov, A. V.; Kauppinen, E. I.; Kaiser, U.; Meyer, J. C. (ACS Nano, 2012)

(untitled) - Liu, H.; Zhang, Y.; Li, R.; Sun, X.; Désilets, S.; Abou-Rachid, H.; Jaidann, M.; Lussier, L.-S. (Carbon, 2010)

(untitled) - Maldonado, S.; Morin, S.; Stevenson, K. J. (Carbon, 2006)

(untitled) - Podila, R.; Chacón-Torres, J.; Spear, J. T.; Pichler, T.; Ayala, P.; Rao, A. M. (Appl. Phys. Lett., 2012)

(untitled) - Sheng, Z.-H.; Shao, L.; Chen, J.-J.; Bao, W.-J.; Wang, F.-B.; Xia, X.-H. (ACS Nano, 2011)

(untitled) - Lu, Y.-F.; Lo, S.-T.; Lin, J.-C.; Zhang, W.; Lu, J.-Y.; Liu, F.-H.; Tseng, C.-M.; Lee, Y.-H.; Liang, C.-T.; Li, L.-J. (ACS Nano, 2013)

(untitled) - Pichler, T.; Knupfer, M.; Golden, M. S.; Haffner, S.; Friedlein, R.; Fink, J.; Andreoni, W.; Curioni, A.; Keshavarz-K, M.; Bellavia-Lund, C.; Sastre, A.; Hummelen, J.-C.; et al. (Phys. Rev. Lett., 1997)

(untitled) - Panchakarla, L. S.; Subrahmanyam, K. S.; Saha, S. K.; Govindaraj, A.; Krishnamurthy, H. R.; Waghmare, U. V.; Rao, C. N. R. (Adv. Mater., 2009)

(untitled) - Li, X.; Wang, H.; Robinson, J. T.; Sanchez, H.; Diankov, G.; Dai, H. (J. Am. Chem. Soc., 2009)

(untitled) - Long, D.; Li, W.; Ling, L.; Miyawaki, J.; Mochida, I.; Yoon, S.-H. (Langmuir, 2010)

(untitled) - Qu, L.; Liu, Y.; Baek, J.-B.; Dai, L. (ACS Nano, 2010)

(untitled) - Wang, Y.; Shao, Y.; Matson, D. W.; Li, J.; Lin, Y. (ACS Nano, 2010)

(untitled) - Zhang, C.; Fu, L.; Liu, N.; Liu, M.; Wang, Y.; Liu, Z. (Adv. Mater., 2011)

(untitled) - Deng, D.; Pan, X.; Yu, L.; Cui, Y.; Jiang, Y.; Qi, J.; Li, W.-X.; Fu, Q.; Ma, X.; Xue, Q.; Sun, G.; Bao, X. (Chem. Mater., 2011)

(untitled) - Sun, C. Q.; Sun, Y.; Nie, Y. G.; Wang, Y.; Pan, J. S.; Ouyang, G.; Pan, L. K.; Sun, Z. (J. Phys. Chem. C, 2009)

(untitled) - Gammon, W. J.; Kraft, O.; Reilly, A. C.; Holloway, B. C. (Carbon, 2003)

(untitled) - Rocha, A. R.; Rossi, M.; da Silva, A. J. R.; Fazzio, A. (J. Phys. D: Appl. Phys., 2010)

(untitled) - Fujimoto, Y.; Saito, S. (Phys. Rev. B, 2011)

(untitled) - Telychko, M.; Mutombo, P.; Ondráček, M.; Hapala, P.; Bocquet, F. C.; Kolorenč, J.; Vondráček, M.; Jelínek, P.; Švec, M. (ACS Nano, 2014)

(untitled) - Gong, K.; Du, F.; Xia, Z.; Durstock, M.; Dai, L. (Science, 2009)

(untitled) - Shan, B.; Cho, K. (Chem. Phys. Lett., 2010)

(untitled) - Arenal, R.; March, K.; Ewels, C. P.; Rocquefelte, X.; Kociak, M.; Loiseau, A.; Stéphan, O. (Nano Lett., 2014)

(untitled) - Pels, J. R.; Kapteijn, F.; Moulijn, J. A.; Zhu, Q.; Thomas, K. M. (Carbon, 1995)

(untitled) - Lee, D. H.; Lee, W. J.; Kim, S. O. (Nano Lett., 2009)

(untitled) - Kundu, S.; Nagaiah, T. C.; Xia, W.; Wang, Y.; Dommele, S. V.; Bitter, J. H.; Santa, M.; Grundmeier, G.; Bron, M.; Schuhmann, W.; Muhler, M. (J. Phys. Chem. C, 2009)

(untitled) - Sharifi, T.; Hu, G.; Jia, X.; Wågberg, T. (ACS Nano, 2012)

(untitled) - Kroke, E.; Schwarz, M. (Coord. Chem. Rev., 2004)

(untitled) - Ewels, C. P.; Erbahar, D.; Wagner, P.; Rocquefelte, X.; Arenal, R.; Pochet, P.; Rayson, M.; Scardamaglia, M.; Bittencourt, C.; Briddon, P. (Faraday Discuss., 2014)

(untitled) - Wiggins-Camacho, J. D.; Stevenson, K. J. (J. Phys. Chem. C, 2009)

(untitled) - Kramberger, C.; Thurakitseree, T.; Koh, H.; Izumi, Y.; Kinoshita, T.; Muro, T.; Einarsson, E.; Maruyama, S. (Carbon, 2013)

(untitled) - Kweon, K. E.; Hwang, G. S. (Phys. Rev. B, 2010)

(untitled) - Hanafusa, A.; Muramatsu, Y.; Kaburagi, Y.; Yoshida, A.; Hishiyama, Y.; Yang, W.; Denlinger, J. D.; Gullikson, E. M. (J. Appl. Phys., 2011)

(untitled) - Faccio, R.; Fernández-Werner, L.; Pardo, H.; Goyenola, C.; Ventura, O. N.; Mombrú, A. W. (J. Phys. Chem. C, 2010)

(untitled) - Czerw, R.; Terrones, M.; Charlier, J.-C.; Blase, X.; Foley, B.; Kamalakaran, R.; Grobert, N.; Terrones, H.; Tekleab, D.; Ajayan, P. M.; Blau, W.; Rühle, M.; et al. (Nano Lett., 2001)

(untitled) - Gai, P.; Stephan, O.; McGuire, K.; Rao, A.; Dresselhaus, M.; Dresselhaus, G.; Colliex, C. (J. Mater. Chem., 2004)

(untitled) - Ayala, P.; Reppert, J.; Grobosch, M.; Knupfer, M.; Pichler, T.; Rao, A. M. (Appl. Phys. Lett., 2010)

(untitled) - Ayala, P.; Plank, W.; Grüneis, A.; Kauppinen, E.; Rümmeli, M.; Kuzmany, H.; Pichler, T. (J. Mater. Chem., 2008)

(untitled) - Kim, Y. A.; Fujisawa, K.; Muramatsu, H.; Hayashi, T.; Endo, M.; Fujimori, T.; Kaneko, K.; Terrones, M.; Behrends, J.; Eckmann, A.; Casiraghi, C.; Novoselov, K. S.; et al. (ACS Nano, 2012)

(untitled) - Sheng, Z.-H.; Gao, H.-L.; Bao, W.-J.; Wang, F.-B.; Xia, X.-H. (J. Mater. Chem., 2012)

(untitled) - Tang, Y.-B.; Yin, L.-C.; Yang, Y.; Bo, X.-H.; Cao, Y.-L.; Wang, H.-E.; Zhang, W.-J.; Bello, I.; Lee, S.-T.; Cheng, H.-M.; Lee, C.-S. (ACS Nano, 2012)

(untitled) - Wang, H.; Zhou, Y.; Wu, D.; Liao, L.; Zhao, S.; Peng, H.; Liu, Z. (Small, 2013)

(untitled) - Jung, S.-M.; Choi, I. T.; Lim, K.; Ko, J.; Kim, J. C.; Lee, J.-J.; Ju, M. J.; Kim, H. K.; Baek, J.-B. (Chem. Mater., 2014)

(untitled) - Maciel, I. O.; Campos-Delgado, J.; Cruz-Silva, E.; Pimenta, M. A.; Sumpter, B. G.; Meunier, V.; López-Urías, F.; Muñoz-Sandoval, E.; Terrones, H.; Terrones, M.; Jorio, A. (Nano Lett., 2009)

(untitled) - Campos-Delgado, J.; Maciel, I. O.; Cullen, D. A.; Smith, D. J.; Jorio, A.; Pimenta, M. A.; Terrones, H.; Terrones, M. (ACS Nano, 2010)

(untitled) - Ruiz-Soria, G.; Susi, T.; Sauer, M.; Yanagi, K.; Pichler, T.; Ayala, P. (Carbon, 2015)

(untitled) - Li, R.; Wei, Z.; Gou, X.; Xu, W. (RSC Adv., 2013)

(untitled) - Choi, C. H.; Chung, M. W.; Kwon, H. C.; Park, S. H.; Woo, S. I. (J. Mater. Chem. A, 2013)

(untitled) - Yu, D.; Xue, Y.; Dai, L. (J. Phys. Chem. Lett., 2012)

(untitled) - Liu, J.; Liu, H.; Zhang, Y.; Li, R.; Liang, G.; Gauthier, M.; Sun, X. (Carbon, 2011)

(untitled) - Gorham, J.; Torres, J.; Wolfe, G.; d’Agostino, A.; Fairbrother, D. H. (J. Phys. Chem. B, 2005)

(untitled) - Puziy, A. M.; Poddubnaya, O. I.; Socha, R. P.; Gurgul, J.; Wisniewski, M. (Carbon, 2008)

(untitled) - Larrude, D. G.; Maia da Costa, M. E. H.; Monteiro, F. H.; Pinto, A. L.; Freire, F. L., Jr (J. Appl. Phys., 2012)

(untitled) - Mowbray, D. J.; Ayala, P.; Pichler, T.; Rubio, A. (Mater. Express, 2011)